(D)rifting in the 21st century: key processes, natural hazards, and geo-resources - F. Zwaan; F. Zwaan; T. M. Alves; P. Cadenas; P. Cadenas; M. Gouiza; M. Gouiza; J. J. J. Phethean; S. Brune; S. Brune; A. C. Glerum (Solid Earth, 2024)
Rifting and continental break-up are major research topics within geosciences, and a thorough understanding of the processes involved as well as of the associated natural hazards and natural resources is of great importance to both science and society. As a result, a large body of knowledge is available in the literature, with most of this previous research being focused on tectonic and geodynamic processes and their links to the evolution of rift systems. We believe that the key task for researchers is to make our knowledge of rift systems available and applicable to face current and future societal challenges. In particular, we should embrace a system analysis approach and aim to apply our knowledge to better understand the links between rift processes, natural hazards, and the geo-resources that are of critical importance to realise the energy transition and a sustainable future. The aim of this paper is therefore to provide a first-order framework for such an approach by providing an up-to-date summary of rifting processes, hazards, and geo-resources, followed by an assessment of future challenges and opportunities for research. We address the varied terminology used to characterise rifting in the scientific literature, followed by a description of rifting processes with a focus on the impact of (1) rheology and stain rates, (2) inheritance in three dimensions, (3) magmatism, and (4) surface processes. Subsequently, we describe the considerable natural hazards that occur in rift settings, which are linked to (1) seismicity, (2) magmatism, and (3) mass wasting, and provide some insights into how the impacts of these hazards can be mitigated. Moreover, we classify and describe the geo-resources occurring in rift environments as (1) non-energy resources, (2) geo-energy resources, (3) water and soils, and (4) opportunities for geological storage. Finally, we discuss the main challenges for the future linked to the aforementioned themes and identify numerous opportunities for follow-up research and knowledge application. In particular, we see great potential in systematic knowledge transfer and collaboration between researchers, industry partners, and government bodies, which may be the key to future successes and advancements.